How to Create Automatically Graded Spreadsheets for Statistics Courses - LoSchiavo, Frank M. (Teaching of psychology, 2016)
Instructors often use spreadsheet software (e.g., Microsoft Excel) in their statistics courses so that students can gain experience conducting computerized analyses. Unfortunately, students tend to make several predictable errors when programming spreadsheets. Without immediate feedback, programming errors are likely to go undetected, and as a result, students will likely encounter difficulty mastering this new skill. In this article, I share techniques for creating spreadsheets that grade themselves either by providing immediate feedback or by delaying feedback until instructors have completed necessary evaluations of student performance. Students prefer automatically graded spreadsheets to more traditional methods for checking answers, and in the long run, automatically graded spreadsheets can save instructors’ valuable time. Furthermore, the techniques that I discuss can be adapted to create automatically graded assignments for other courses.